Comparative analysis of upper extremity performance variables in elite and novice recurve archers: A cross-sectional observational study - Ganjave, P. D.; Dabholkar, A. S. (International Journal of Life science and Pharma Research, 2021)
Scapular stability, grip strength, and fine motor skills are found to be the important variables to achieve the highest performance in precision tasks. Archery being one of the precision games, understanding these variables in archers is crucial as they can influence shooting performance. Therefore, the purpose of the present study was to compare the fine motor skill, hand grip strength and scapular stability in elite and novice recurve archers.50 Novice and 50 Elite recurve archers in the age group of 15-25 years were recruited. Scapular stability was assessed by Scapular dyskinesis test, hand grip strength by baseline hydraulic hand dynamometer for both upper limbs (bow arm and draw arm) & fine motor skill was assessed by Purdue pegboard. The results were analysed using SPSS software, version 16.00. Independent T-test and Mann Whitney U test were performed for between-group comparisons. Elite archers [draw arm (27.02±7.08), bow arm (26.16±7.31) CI- 95%] showed statistically significant greater hand grip strength [draw arm (p=0.039), bow arm (p=0.008)] than novice archers [draw arm (23.92 ±7.73), bow arm (22.04 ± 7.86) CI-95%]. In assembly tasks for fine motor skill, elite archers [(34.44 ±3.92) CI-95%] showed significantly better coordination (p=0.011) than novice archers [(31.78±6.14) CI-95%]. For scapular stability, elite archers showed significant scapular dyskinesia on the draw arm (p=0.005) and bow arm (p=0.012)] than novice archers. Elite recurve archers had significantly better hand grip strength and fine motor skill than novice recurve archers. However, 52% subtle and 18% obvious scapular dyskinesia was observed in elite archers than novice archers who showed 38% subtle and 8% obvious scapular dyskinesis. The results of the study indicate that elite archers had statistically significant hand grip strength for both arms, fine motor skills, and a greater presence of obvious and subtle scapular dyskinesis than novice archers.